A new role of family 32 carbohydrate binding module in alginate lyase from Vibrio natriegens SK42.001 in altering its catalytic activity, thermostability and product distribution. (August 2021) - Meng, Qing; Zhou, Licheng; Hassanin, Hinawi A.M.; Jiang, Bo; Liu, Yongchuang; Chen, Jingjing; Zhang, Tao
Abstract: Alginate lyase has been widely investigated to degrade alginate into oligomers, which possess potential physiological benefits including antidiabetic and anti-inflammation activities. Some alginate lyases are multidomain enzymes, in which carbohydrate binding modules (CBMs) are generally considered as accessory modules besides catalytic domain, and exhibit diverse functions such as enhancing catalytic efficiency, substrate recognition and binding. However, it remains difficult to accurately predict CBM functions in certain carbohydrate active enzymes, and it is important to identify and characterize more CBM-containing alginate lyase thus providing foremost insights into the catalysis mechanisms. In the present study, a new NaCl-activated alginate lyase Aly01 was identified from Vibrio natriegens SK42.001, which contained a CBM32 domain and a catalytic domain linked by a helix linker and a random coil linker. CBM32-cleaved truncation presented an activity of 3779.4 ± 92.2 U μmol −1, retaining only 60% that of the full-length Aly01 (6276.0 ± 210.7 U μmol −1 ). With the further truncation of the helix linker and the random coil linker, the activities dropped to 1278.6 ± 23.9 and 398.7 ± 44.4 U μmol −1, respectively. Besides, CBM32 truncation resulted in thermostability decline of Aly01 by 60% after 30-min incubation at 35 °C, and altered its character of specifically releasing trisaccharide product. Docking study further confirmed that both CBM32 and catalytic domain interacted with the substrate in the degradation process. This study expands the underexplored CBM diversity in carbohydrate active enzymes and lays a foundation of enhancing catalytic efficiency and altering the product distribution by performing operation on CBM domains. Highlights: A new CBM32-containing alginate lyase Aly01 was identified and characterized. CBM32 enhanced catalytic efficiency and thermostability of Aly01. Truncation of CBM32 altered the product distribution of Aly01. Helix linker between CBM32 and catalytic domain may determine the product length.